THE EFFECT OF TEMPERATURE VARIATIONS ON THE DEACETYLATION PROCESS OF CHITOSAN CHARACTERISTICS FROM MUD CRAB (SCYLLA SERRATA) SHELL WASTE - Hasriani; Olii, AudiaTriani; Najib, Ahmad (Universal Journal of Pharmaceutical Research, 2024)
Aim and objective: The aim of this study was to determine the yield value, moisturization, ash, and degree of deacetylation by the variations in deacetylation temperature effect on the quality of chitosan. Methods: In the synthesis process of chitosan, the first step was demineralization, followed by deproteinization. Afterward, the deacetylation process synthesized the material with temperature variations of 80, 100, and 120ºC. Furthermore, it was characterized by moisture, ash content, and degree of deacetylation. The last step was the Fourier Transform Infra-Red Spectrophotometer (FT-IR) to determine the complete chitosan synthesis. Results: The results of this study showed that the chitosan yield and water content met the requirements of the quality standards of chitosan. The values obtained were high, which was affected by the temperature. However, the ash content and degree of deacetylation did not meet the requirements of chitosan quality standards. FTIR data showed that the -OH functional group, a -NH group, and no -C=O group from the amide group were found to have characteristics of chitosan formation. Conclusion: Mud crab shell waste is a potent raw material for making chitosan. The study also reported that the production of chitosan from mud crab shell waste is affected by temperature. Peer Review History: Received 19 May 2024; Reviewed 24 July 2024; Accepted 27 August; Available online 15 September 2024 Academic Editor: Prof. Dr. Gorkem Dulger , Duzce University, Turkey, gorkemdulger@yandex.com Reviewers: Prof. Hüsniye Kayalar, Ege University, Turkey, husniyekayalar@gmail.com Prof. Ali Gamal Ahmed Al-kaf, Sana’a university, Yemen, alialkaf21@gmail.com